P05.23 Local recurrence and leptomeningeal dissemination after resection of brain metastases: a single-institution, retrospective study in the era of individualized treatment. (19th September 2018) - Nakasu, Y; Mitsuya, K; Deguchi, S; Hayashi, N; Harada, H; Nakasu, S
Abstract: Background: Metastases are the most frequent tumours in the brain, and need to be managed by a multimodality team. Surgical resection of brain metastases contributes to immediate improvement of patients' performance status. We retrospectively analyzed postoperative local recurrence and leptomeningeal dissemination that influence outcome in patients who underwent resection and adjuvant radiation therapy. Material and Methods: One hundred and seventy-three patients who underwent resection surgery for newly diagnosed brain metastases in our institution between 2002 and 2015 were included in this study. Our cancer board determined the individualized indication of treatments for each patient, and supported patient's decision making. Primary cancers were lung (36.4%), colon (16.2%), breast (11.0%) and others. Results: A majority of patients (88.4%) underwent minimum resection without safety margin around tumour. Surgical procedures caused no permanent morbidities. Eighty-seven percent of patients underwent postoperative adjuvant radiotherapy. The median overall survival time from brain surgery was 9.8 months. Thirty of 173 patients (17.3%) developed local recurrence and 14 (8.1%) developed leptomeningeal carcinomatosis. Male sex (HR: 2.8, 95%CI: 1.0–10.0), colon cancer (HR: 6.5, 95%CI: 2.2–24.2), and no postoperative radiation (HR: 5.6, 95%CI: 2.1–13.7) were identified as risk factors of local recurrence in multivariate analysis. Female sex (HR: 4.4, 95%CI: 1.2–20.9) and recursive partitioning analysis class 3 (HR: 1.0e+9, 95%CI: 1.7-) were identified as risk factors of leptomeingeal dissemination in multivariate analysis. Conclusion: Our retrospective review showed that individualized treatment with surgical resection followed by adjuvant radiation therapy is a safe and feasible method for brain metastases with reasonable local control and infrequent dissemination in the real world.